Horror culture in the new millennium digital dissonance and technohorror - Powell, Daniel (Daniel W.) (Lexington Books, 2019)
"Horror Culture in the New Millienium surveys horror culture in the first two decades of the new millennium through a series of critical essays on the changing character of dark storytelling. It is a journey both into the complexity of the evolution of communication and the stories we tell about what it means to be human"--